Decentralisation and Constitutional Law in Indonesia: Balancing Regional Autonomy and National Unity - Irman Putra; Arief Fahmi Lubis (West Science Law and Human Rights, 2024)
This paper examines the normative aspects of decentralization and constitutional law in Indonesia, focusing on the balance between regional autonomy and national unity. Through a doctrinal analysis of constitutional provisions, key legislation, and judicial interpretations, alongside qualitative case studies, the study explores how Indonesia has navigated the complex relationship between empowering local governance and maintaining a cohesive national identity. The findings reveal that while the legal framework provides for significant regional autonomy, challenges remain in ensuring uniformity in law enforcement, addressing regional disparities, and preventing fragmentation. The study highlights the need for a nuanced approach to decentralization that accommodates regional diversity while fostering national unity, offering recommendations for strengthening local governance, enhancing equitable resource distribution, and refining the legal and regulatory frameworks.